Transmisión y reactivación del legado de Víctor Jara y la Unidad Popular en un festival político en Gales. - Rivera-Volosky, Ignacio (Studies in Latin American Popular Culture, 2023)
In this article, I analyze a Welsh festival inspired by Chilean artist Víctor Jara and the government of Popular Unity (1970–1973). Using the theory of cultural performance, and based on interviews with participants and observations of some activities carried out in the festival, I argue that the festival is a space that simultaneously acts both to suspend and to create political normativity. On the one hand, the politics of the festival proposes a transgression of the political normativity and hegemony of neoliberalism in the United Kingdom and the West. On the other hand, the festival reinforces a political identity inspired by progressive, anti-neoliberal movements and governments in Latin America. These processes of subversion and reinforcement are mutually interconnected since the reinforcement of the political normativity of social progressist governments and movements in Latin America is constituted as a form of transgression of the neoliberal, conservative political agenda that is currently hegemonic in the contemporary British government and in some Latin American countries.